Development of high performance materials based on bamboo through densification process - Kadivar, Marzieh (2020)
Due to its sustainability, reliability, excellent physical and mechanical properties, and ease of access, bamboo has become an attractive material for engineering applications. However, several problems, such as heterogeneous properties and durability issues, still hinder the widespread use of bamboo as a building material. Therefore, bamboo undergoes special treatments and processes to solve these difficulties. Densification processes can be applied to decrease the heterogeneity of bamboo culms, enhance its mechanical performance, and consequently help using bamboo more efficiently as an industrial material in modern constructions. Reviewing the literature on bamboo densification suggests that initial moisture content, densification degree, temperature, and compression rate are the main effective parameters of the process. Therefore, the experimental studies in this thesis have been oriented to achieve optimal parameters for the densification process. First, the influence of initial moisture content on thermo-mechanical (TM) densification of bamboo was investigated through mechanical, chemical, and physical characterizations. The results of this step showed that the densification process increases density and all related bending properties (modulus of rupture (MOR), modulus of elasticity (MOE), the limit of proportionality (LOP), and specific energy (SE)) of bamboo. The densified samples with 10% initial moisture content presented the best bending properties, with an average MOR, MOE, and dynamic MOE of 318 MPa, 72.2 GPa, and 34.1 GPa respectively, with an increase of 56% for MOR and 41% for MOE in comparison with un-densified counterparts. SEM analysis of bamboo cross-sections showed the rearrangement of fibers, dense compaction of vascular bundles, and partial closure of cavities as results of densification. Physical characterization analyses revealed that the densification process was detrimental to the dimensional stability of bamboo. Therefore, in a second study, TM modification parameters (temperature, compression rate, and pressing time) were optimized to achieve the best dimensional stability through spring back (change of thickness with time after densification), water absorption, and thickness swelling measurements. According to the results of this step, the maximum achievable DD in which no shear failure and no lateral deformation occurs is about 43.6%, which can be obtained by densifying bamboo at 200 °C with a compression rate of 2 mm/min. X-ray densitometry analysis confirmed that the highest value of density, 1.30 g.cm-3, is achieved with a DD of around 50%. The lowest values of spring back, water absorption, and thickness swelling, i.e., 4.72%, 23.80%, and 17.70% respectively, for densified bamboo, are obtained when the densification process is conducted at 200 °C with a compression rate of 6.73 mm/min. Lastly, two examples of application for densified bamboo were suggested; flattened-densified bamboo and bamboo sandwich panel. In conclusion, significant gains in bamboo performance could be obtained with the densification process.